IMPLEMENTASI HUKUM PAJAK DAN PEMUNGUTAN PAJAK BAGI KESEJAHTERAAN SOSIAL RAKYAT INDONESIA - Arif Sofiyan Berlianto; Taun (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
Taxes are obligatory contributions of individuals or entities to the state as a legal obligation, there is no direct incentive to use them to meet the greatest needs for the prosperity of the people of the nation. To regulate taxation, a tax law is needed, namely a collection of regulations. This regulates the relationship between the government as a tax collector and the public as a tax payer. So that the Government places tax obligations as one of the embodiments of state obligations which are a means of financing the state in national development in order to achieve the goals of the State because most taxes constitute national income. This writing aims to determine the applicable tax collection in Indonesia for the welfare of the people and its implementation according to the applicable tax law to reduce tax problems.